Faktor-Faktor yang Berhubungan dengan Pemeriksaan Kehamilan (K4) di Puskesmas Buay Pemaca Kabupaten Ogan Komering Ulu (OKU) Selatan Tahun 2021 - Isnaini Isnaini; Rizki Amalia; Siti Aisyah; Dewi Ciselia (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
According to the World Health Organization (WHO) in 2017, the maternal mortality rate (MMR) is still very high, around 810 women die from complications related to pregnancy or childbirth worldwide every day, and around 295,000 women die during and after pregnancy and childbirth. Efforts to accelerate the reduction of the Maternal Mortality Rate (MMR) are carried out by ensuring that every mother is able to access quality maternal health services. The low number of pregnant women who do can be influenced by several factors. The factors that influence pregnant women to perform antenatal care are knowledge, attitudes, parity, economy, socio-culture, education and husband's support. The purpose of this study was to determine the relationship between knowledge, education and husband's support with antenatal care at the Keramasan Health Center Palembang in 2021. The research design used an Analytical Survey with a Cross Sectional approach. The population in this study were pregnant women in the third trimester (gestational age of more than 28-40 weeks) who came to check their pregnancy in August - September at the Keramasan Palembang Health Center, totaling 64 people. The sampling technique in this study was carried out by accidental sampling with a total sample of 64 respondents. Data collection using a questionnaire sheet. Data analysis using univariate analysis and bivariate analysis using chi square test. The results of the study showed that there was a relationship between knowledge (p value = 0.037), education (p value = 0.013) and husband's support (p value = 0.008) with pregnancy examinations at the Keramasan Health Center Palembang in 2021. It is hoped that the results of this study can be an illustration for the puskesmas to can further increase the visits of pregnant women in their working areas by providing information to pregnant women about the schedule and benefits of prenatal care.